Healthy Volunteers in Commercial Clinical Drug Trials : When Human Beings Become Guinea Pigs - Mwale, Shadreck (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book provides a richly detailed contribution to the understanding of healthy volunteer experiences in clinical drug trials in the UK. Contemporary society, especially the West, has seen a significant increase in the production and use of pharmaceutical products, particularly for disease treatment. However, despite the large numbers of people involved, particularly in the UK, very little is known about their experiences in commercial phase I clinical drug trials. Shadreck Mwale critiques common conceptions of the terms 'volunteer' and 'altruism' as used in policy and practice of human involvement in clinical trials and calls for an awareness of the complexity of the terms and how the social contexts participants find themselves in shape acts of voluntarism. Based on extensive empirical evidence and conceptual analysis, the book presents new insights into the lives of healthy volunteers, challenges bioethical conceptions and generates new frameworks for policy and practice of FIHCTs. It will be of particular interest to scholars and practitioners in the wider social sciences, medical Sociology and medical anthropology, pharmacology and bioethics.